2020
DOI: 10.21203/rs.3.rs-37055/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epitope-based Immunoinformatics Approach on Nucleocapsid Protein of Severe Acute Respiratory Syndrome-Coronavirus-2

Abstract: With an increasing fatality rate, severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) has emerged as a promising threat to human health worldwide. SARS-CoV-2 is a member of the Coronaviridae family, which is transmitted from animal to human and because of being contagious, further it transmitted human to human. Recently, the World Health Organization (WHO) has announced the infectious disease caused by SARS-CoV-2, which is known as coronavirus disease-2019 (COVID-2019) as a global pandemic. But, no sp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 47 publications
2
4
0
Order By: Relevance
“…28,29 However, few reports on the study of that can recognize MHC. [30][31][32][33][34][35] In the present study, N3-1 was also identified as a B cell epitope detected by MAb K1-175.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…28,29 However, few reports on the study of that can recognize MHC. [30][31][32][33][34][35] In the present study, N3-1 was also identified as a B cell epitope detected by MAb K1-175.…”
Section: Discussionsupporting
confidence: 65%
“…SARS‐CoV‐2 NP epitopes stimulate the immune system to release various cytokines through helper T‐lymphocytes and antigen‐presenting cells, leading to the activation of cytotoxic T‐lymphocytes and B‐cell lymphocytes to lyse infected cells and kill pathogens. Based on immunoinformatics and epitope information from the Immune Epitope Database and Analysis Resource, N1‐3 and N4‐8 are B‐cell epitopes, while the N3‐1 epitope is a T‐cell epitope that can recognize MHC 30–35 . In the present study, N3‐1 was also identified as a B cell epitope detected by MAb K1‐175.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Although several kinds of research are being carried out in famous laboratories in several countries, vaccine development for disease is usually time-consuming. Despite there being plenty of experimental trials associated with COVID-19 treatment and medications, as of yet, scientists are still on the hunt for specific therapeutic drugs [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the epidemiologic features of SARS-COV-2 virus [19,20], its clinical manifestations in different patient groups [21,22], and its molecular characteristics [23][24][25], as well as health systems response [26], economic and social consequences [27][28][29], and public attitudes toward the measures implemented in Bangladesh have been investigated [30][31][32], public perceptions of pandemic management efforts by the responsible bodies have never been studied. Motivated by the work of Bigdeli et al, we decided to explore the public perceptions of COVID-19 pandemic management in Bangladesh by focusing on the relationships between (1) people and the decision-makers (or the larger health system governance), (2) people and the service providers (only physicians were covered in this study), and (3) service providers and decision-makers [33].…”
Section: Introductionmentioning
confidence: 99%